2012
DOI: 10.1142/s1793524511001453
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Binge Drinking

Abstract: We develop a two-stage (four component) model for youths with serious drinking problems and their treatment. The youths with alcohol problems are split into two classes, namely those who admit to having a problem and those who do not. It is shown that the model possesses two steady states, one where people have no alcohol problems and one where there is an endemic state involving those with an alcohol problem. The stability of these states is analyzed and a threshold established such that each state will be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…The three subpopulations are similar to the classes defined in the work of Sanchez et al [36] (also see Benedict [3]) and Mulone and Straughan [30], however neither of these models allow for total recovery. Sanchez et al [36] found that the basic reproduction number alone is not always the key factor in controlling drinking in the population.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…The three subpopulations are similar to the classes defined in the work of Sanchez et al [36] (also see Benedict [3]) and Mulone and Straughan [30], however neither of these models allow for total recovery. Sanchez et al [36] found that the basic reproduction number alone is not always the key factor in controlling drinking in the population.…”
Section: Introductionmentioning
confidence: 54%
“…Following the method in Mulone and Straughan [30], we now introduce the variables s(t) = S(t)/N , a(t) = A(t)/N and r(t) = R(t)/N , which enables us to rewrite system (2.1)…”
Section: The Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations